Peralihan Kerajaan Islam Secara Damai dari Hasan bin Ali Kepada Muawiyah bin Abi Sufyan - Noer Adektya Ekaviana (Qurthuba: The Journal of History and Islamic Civilization, 2021)
Abstract: This article examines the causes, processes, and impacts resulting from the transfer of Islamic power from Hasan to Muawiyah. The approach is a political history with theoretical analysis using the theory of power from Max Weber. The results of this study show the event of political transition that involved two important figures namely Muawiyah and Hasan was caused by several factors. The process also had consequences for the life of Muslims in many aspects. The results that the conflict between Kubu Muawiyah and Hasan is a remnant of the earlier conflict between the Islamic community and its rulers. Utamanya ever since Utsman Bin Affan's early days. The most striking aspect of these two historical figures' combined efforts to find a solution to the damai problem in order to end the persecutory berdarah between Muslims is their use of catatan emas as a result of their pragmatism and leadership. Keywords: political transition, Muawiyah, Hasan, Islam, unity